Star Trek : strange new worlds -- the Scorpius run - Parrott, Ryan (Comic book author); Johnson, Mike (Comic book author) (IDW Publishing, 2024)
Set course with Captain Pike and the crew of the U.S.S. Enterprise to the Scorpius Constellation as they become the first Federation vessel to explore this uncharted region of space! In this romp across the stars, the Enterprise crew learn what it truly means to explore the strange and unfamiliar when they lose contact with Starfleet and everything outside the region. After entering a crime lord’s starship competition to save an innocent pilot, the Enterprise jets through a gauntlet of dangerous environments in the unexplored Scorpius sector. But cosmic storms and sentient ship-eating asteroids aren’t the only obstacles the crew will have to survive!